KOMUNIKASI VERTIKAL DAN HORIZONTAL ANTARA PUSTAKAWAN DAN PEMUSTAKA DALAM LAYANAN PERPUSTAKAAN PERSFEKTIF ISLAM - Mustofa, Muhamad Bisri; Wuryan, Siti; Husnita, Tri Jely (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2021)
Communication provides the delivery of messages or information between librarians and users in order to produce good communication. Library is a place to get information from a librarian according to the needs of the visitors so that an effective communication process can occur. To carry out good communication between librarians and users, a vertical and horizontal communication is needed, each of which has a different purpose. Vertical communication consists of downward and upward communication, downward communication, namely communication that conveys messages between leaders and subordinates, while upward communication is communication between subordinates and superiors and horizontal communication is horizontal or sideways communication between coworkers. The research method uses an analytical method that provides ideas and data collection in research, in library services with a more Islamic perspective, librarians believe in prophetic values ​​in the form of communication delivered through the Koran. The services used are social inclusion supported in education